2014
DOI: 10.1007/s11606-014-3082-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Requests on Provider-Perceived Visit Difficulty in Primary Care

Abstract: BACKGROUND: "Difficult visits" are common in primary care and may contribute to primary care provider (PCP) career dissatisfaction and burnout. Patient requests occur in approximately half of primary care visits and may be a source of clinician-patient miscommunication or conflict, contributing to perceived visit difficulty. OBJECTIVE: We aimed to determine associations between types of patient requests and PCP-perceived visit difficulty. DESIGN: This was an observational study, nested in a multicenter randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 32 publications
2
30
1
1
Order By: Relevance
“…A watchful waiting approach may also improve the physician experience by reducing the greater perceived difficulty of visits with patients who request diagnostic tests. 8 Although previous observational analyses suggested that patient-centered communication may be associated with lower overall diagnostic testing, 1,14 more patient-centered communication was not associated with test ordering in our study. While prior studies have examined practice patterns among physicians with more versus less patient-centered communication styles, our study examined the association between patientcenteredness and test ordering within a specific visit when a low-value test was requested.…”
Section: Discussioncontrasting
confidence: 72%
“…A watchful waiting approach may also improve the physician experience by reducing the greater perceived difficulty of visits with patients who request diagnostic tests. 8 Although previous observational analyses suggested that patient-centered communication may be associated with lower overall diagnostic testing, 1,14 more patient-centered communication was not associated with test ordering in our study. While prior studies have examined practice patterns among physicians with more versus less patient-centered communication styles, our study examined the association between patientcenteredness and test ordering within a specific visit when a low-value test was requested.…”
Section: Discussioncontrasting
confidence: 72%
“…In addition, clinicians know that many patients believe that more health care is better than less health care 11. As a result, clinicians may find it difficult to deny requests for specific services,12 and they could preemptively order tests to avoid eliciting such requests from patients 613 …”
Section: Introductionmentioning
confidence: 99%
“…42, 43 Another important construct was the presence of negotiation between patients and clinicians (operationalized as patient requests and clinician recommendations). Negotiation around diagnosis and treatment has been linked to clinician-reported visit difficulty 39, 44 and is important in communication about other commonly contested medical problems. 45, 46 Other communication patterns that we considered likely to be associated with the outcomes of interest included patient assessments of their physical pain and assessments of pain treatment options.…”
Section: Methodsmentioning
confidence: 99%
“…We advanced H2b because two prior studies found that patient requests for diagnostic tests were associated with more difficult visits. 39, 44 As noted above, request subcategories (such as requests for diagnostic tests) were too infrequent to analyze separately; therefore, we analyzed patient requests for action as a group. Finally, we hypothesized that, even though patients and clinicians often agree on treatment plans by the end of a visit, 8 discussion of opioid risks would be associated with greater visit difficulty (H1c) given how frequently clinicians report this topic as contentious.…”
Section: Methodsmentioning
confidence: 99%